Thiamin Requirement of Nile Tilapia, Oreochromis niloticus - Lim, Chhorn; Yildirim-Aksoy, Mediha; Barros, Margarida M. [UNESP]; Klesius, Phillip (Wiley, 2011)
Juvenile Nile tilapia, Oreochromis niloticus, were fed to apparent satiation twice daily with purified diets containing 0, 1.0, 2.0, 4.0, 8.0, and 16.0 mg/kg and 0, 2.0, 4.0, 8.0, 16.0, and 32.0 mg/kg of thiamin in separate 14- and 8-wk trials (Experiments 1 and 2, respectively). Fish fed the diet devoid of thiamin developed neurological disorders, anorexia, reduced growth, and feed efficiency and increased mortality (Experiment 2 only) within 4-6 and 8-10 wk for Experiments 2 and 1, respectively. Low red blood cell count (RBC) and hematocrit (Ht) were observed in fish fed the thiamin-deficient diet. Serum pyruvate was elevated in fish fed the thiamin unsupplemented diet. Serum lactate was not affected by dietary thiamin levels. Whole body protein was unaffected by dietary levels of thiamin. Body moisture and ash increased whereas body lipid decreased in fish fed the thiamin unsupplemented diets. None of these abnormalities were observed in fish fed the thiamin-supplemented diets. Using the response curves determined by PROC NLMIXED to estimate dietary thiamin levels required for various response variables, a dietary thiamin level of 3.5 mg/kg diet was adequate for optimum growth, feed intake and efficiency, survival, prevention of neurological symptoms, and maintaining normal levels of RBC, Ht, serum pyruvate, and proximate body composition. © 2011.
Keywords: cichlid; diet; experimental study; lipid; mortality; neurology; survival